Bivalve Community Structure on Mangrove Ecosystem in the Mengkapan Village, Sungai Apit Subdistrict, Siak Regency, Riau Province - Yollanda Defira; Adriman Adriman; Muhammad Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstrackMangrove ecosystem in the Mengkapan Village degraded due to illegal logging, settlements and ecotourism. Condition of   the mangrove  affects the community structure of bivalvesin general.This study was carried out on February - March 2018,  in the Mengkapan Village. The purpose of the study was to determine the structure of bivalves community in the mangrove ecosystem.There were 3 stations and in each stasion  there was 1 transect line with 3 plots (1x1 m). The bivalves present in the plots were collected manually every two weeks.Data were analyzed descriptively. Results shown that there were 4 bivalves species present, there wereGeloina expansa, Polymesoda erosa, Polymesoda bengalensis, and Anadara granosa. Bivalve density range from 10 - 30organism/m2, diversity index H' 0.987 - 1.956, dominance index C 0.264 - 0.509 and similarity index E is 0.017 – 0.132. Temperatures was 25-28°C, with sandy mud substrate, organic material 32.320% - 36.353%, water pH 6-7, soil pH 6 - 7 and salinity 24-26 0/00. The bivalve community structure in Mengkapan Village is classified as medium with the dominant species isP. bengalensis. Keywords: Diversity index H’, Dominance index C, Similarity index E,Pelecypoda, Organicmaterial